A 12-Week Pilot Exercise Program for Inactive Adults With Celiac Disease: Study Protocol - A Justine Dowd PhD; Liam Kronlund MSc; Candice Parmar BSc; Julia T Daun BKin; Kathryn Wytsma-Fisher MKin; Raylene A Reimer PhD; Guillaume Y Millet PhD; S Nicole Culos-Reed PhD (SAGE Publishing, 2019)
Background Individuals with celiac disease must follow a strict gluten-free diet (GFD) in order to avoid negative short- and long-term health consequences. Unfortunately, many people with celiac disease report poor quality of life (QoL) despite following a strict GFD, and up to 30% still report negative symptoms (eg, gastrointestinal upset). Purpose The purpose of the MOVE-C (understanding the relationship between the M icrobi O me, V itality, and E xercise in C eliac disease) pilot study is to explore the effects of a 12-week supervised progressive high-intensity interval training (HIIT) and lifestyle intervention on physiological, behavioral, and psychosocial outcomes among inactive adults with celiac disease. Methods/Design: Sixty inactive adults diagnosed with celiac disease will be randomized to HIIT+ or waitlist control (WLC). Participants in the HIIT+ will engage in a 12-week HIIT + lifestyle education program. HIIT sessions will be comprised of 2 workouts per week, working up to 14 × 30-second intervals at 90% maximal heart rate (HRmax) followed by 2 minutes recovery at 50% HRmax. The 6 biweekly lifestyle sessions will involve education on the promotion of a whole foods GFD, sleep hygiene, psychosocial coping skills (eg, self-compassion), and self-regulatory skills to master changes in behaviors. Assessments will occur at pre and post 12-week intervention and 3-month follow-up. WLC participants will be offered a 12-week HIIT program + online lifestyle education sessions after completing the final assessment. The primary outcomes are QoL and gut microbiota composition assessed with 16S rRNA sequencing. The secondary outcomes are markers of metabolic syndrome (waist circumference, fasting glucose, serum lipids, blood pressure, and body composition), gastrointestinal symptoms, sleep quality, adherence to a GFD, exercise behavior, self-regulatory efficacy, and self-compassion. It is hypothesized that participants in the HIIT+ will experience improvements in all outcomes when compared to those in the WLC. These improvements are expected to be maintained at the 3-month follow-up. Discussion The findings from this study will advance the knowledge regarding the effects of HIIT and lifestyle education on key outcomes for an at-risk chronic disease population. Furthermore, the findings can be used to inform future programs to improve fitness and physical and mental health outcomes for people with celiac disease.